Multijet motion and deviation in electrospinning. Issue 60 (2nd July 2015) - Zheng, Yuansheng; Gong, R. Hugh; Zeng, Yongchun
<x xml:space="preserve">Abstract</x> This study provides a thorough description associated with multijet motion and deviation in electrospinning.